Differential impact of deep intraparenchymal hyperdensities versus subarachnoid/cortical hyperdensities on futile reperfusion after mechanical thrombectomy: a propensity score-matched study - Dong, Meijuan; Wang, Yanfeng; Sun, Bo; Zhou, Ruoyu; An, Kun; Li, Mingchao (Frontiers in Neurology, 2025)
BackgroundDespite successful mechanical thrombectomy (MT), futile reperfusion (FR) remains a major challenge in acute ischemic stroke (AIS). While post-MT hyperdense areas (HDAs) on non-contrast computed tomography (CT) are associated with reperfusion injury, the differential effects of anatomical HDA subtypes—deep intraparenchymal (DIH) versus subarachnoid/cortical (SCH)—on FR risk are unclear.MethodsWe retrospectively analyzed 864 AIS patients undergoing MT (2017–2023). HDAs detected within 0.5 h post-MT were classified as DIH or SCH. Propensity score matching (PSM) balanced baseline confounders (1:1 DIH: SCH). Risk factors for FR were analyzed using a multivariate logistic regression analysis in the PSM cohort.ResultsAfter PSM, 116 patients in the DIH group were matched with 116 patients in the SCH group. In total, 91 patients (78.5%) in the SCH group and 72 patients (62.1%) in the DIH group suffered FR (p = 0.006). A multivariate analysis showed that SCH significantly increased the risk of FR (OR: 3.103, 95%CI: 1.425–6.759, p = 0.004), indicating that patients with SCH have a 3.103 times higher risk of FR than patients with DIH.ConclusionAnatomical HDA subtypes differentially predict FR risk, with SCH portending a worse prognosis. This subtype classification enables early risk stratification and may guide personalized post-MT management.